A case study on improvement of high voltage power distribution system in Intec Campus: article / Kamal Arrifin Mohd Fauzi - Mohd Fauzi, Kamal Arrifin (2011)
Nowadays there were increased in quantity of students at Intec Campus due to target of UiTM management to increase the quantity of students at UiTM for entire campus in Malaysia. These increases of students lead to construct new building in locate students and lecturers hence will increase load demand in Intec Campus. By this increasing of load demand, it has created some problems that related to the high voltage power distribution system of Intec Campus such as the existing one unit 2000kVA transformer at Substation No 1 did not support anymore the load demand thus make it increase in temperature and vibrate due to high load demand. The other problems related to the other substations in Intec Campus will be discussed further in this study later. From the problems, the suggestions will come out at the end of this study in order understand and improve the high voltage system in Intec Campus